Personal Data Protection as an Element of the Ethical Evaluation of Scientific Research Involving Humans (Diametros, 2023)
The aim of the article is to explain the relationship between the ethical evaluation of scientific research involving personal data and the assessment of compliance with data protection law. The article presents the mutual relationship between the protection of personal data and scientific activity from a dogmatic perspective, the legal regulation of the processing of personal data in scientific research, and the so-called research exceptions that apply when data are processed for scientific research. It also covers the importance of meeting the ethical requirements of scientific research in order to profit from the indicated exceptions. Finally, it provides a comparison between the ethical and the legal systems of personal data protection in research (objectives, criteria, authorities, and procedures).
Keywords: proportionality; research; research involving humans; research ethics; ethical standards; ethics committees; personal data protection; GDPR; legal compliance; research exceptions